In-Situ Catalytic Pyrolysis of Spirulina platensis residue (SPR): Effect of Temperature and Amount of C12-4 Catalyst on Product Yield - Siti Jamilatun; Ratih Mahardhika; Imelda Eka Nurshinta; Lukhi Mulia Sithopyta (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2021)
Currently, dependence on fossil energy, especially petroleum, is still high at 96% of the total consumption. One solution to overcome fossil energy consumption is processing alternative energy sources derived from microalgae biomass. This study aims to study the pyrolysis of microalgae with the addition of the C12-4 (Cr2O3+Fe2O3+C+CuO+promoter) catalyst. The biomass used in this study was Spirulina platensis residue (SPR). This study used a fixed bed reactor with an outer diameter of 44 mm, an inner diameter of 40 mm, and a total reactor height of 600 mm. The C12-4 was mixed fifty grams of SPR with a particle size of 100 mesh with a ratio variation of 5, 10, and 15 wt.%. The feed mixture was placed in the reactor (in-situ), and the reactor was tightly closed. The nickel-wire heater wrapped around the reactor wall was employed. The pyrolysis heating rate was 24.33 °C/min on average, and the temperatures were varied as 300, 400, 500, 550, and 600 °C. The research found that the optimum temperature conditions without and with the catalyst to produce bio-oil were different. The pyrolysis without any catalyst (500 ⁰C), with a catalyst of 5 wt.% (500 ⁰C), 10 wt.% (400 ⁰C), and 15 wt.% (550 ⁰C) produced the bio-oil yield of 15.00, 17.92, 16.78 and 16.54, respectively. The use of 5, 10, and 15 wt.% catalysts increased the water phase yield. The char yield was influenced by the amount of catalyst only at 300 ⁰C; i.e., the more catalysts, the less char yield. The pyrolysis without any catalysts produced the highest gas product. A catalyst significantly increased the pyrolysis conversion from 48.69 (without catalyst) to 62.46% (15. wt.% catalyst) at a temperature of 300 ⁰C. The optimum conditions for producing the best bio-oil were at 600 °C and 10 wt.% of catalysts, which resulted in an O/C ratio of 0.14.Keywords: C12-4 catalyst, in-situ catalytic pyrolysis, Spirulina platensis residue, yield bio-oilA B S T R A KKetergantungan terhadap energi fosil khususnya minyak bumi, saat ini masih tinggi yaitu mencapai 96% dari total konsumsi. Salah satu solusi untuk mengatasi ketergantungan energi fosil adalah dengan mengolah sumber energi yang berasal dari biomassa mikroalga. Penelitian ini bertujuan untuk pirolisis mikroalga dengan penambahan katalis C12-4 (Cr2O3 + Fe2O3 + C + CuO + promotor). Sampel yang digunakan adalah residu Spirulina platensis (SPR). Penelitian ini menggunakan reaktor unggun tetap dengan diameter luar 44 mm, diameter dalam 40 mm, dan tinggi reaktor 600 mm. Spirulina platensis dengan ukuran partikel 100 mesh sebanyak 50 gram dicampur dengan katalis C12-4 dengan variasi 5, 10, dan 15 wt.%. Campuran umpan (in-situ) dimasukkan ke dalam reaktor dan ditutup rapat. Pemanas menggunakan arus listrik melalui kawat nikel yang dililitkan pada dinding reaktor. Laju pemanasan pirolisis rata-rata 24,33 °C/menit, variasi suhu 300, 400, 500, 550, dan 600 °C. Kondisi optimum tanpa dan dengan katalis untuk menghasilkan bio-oil memiliki nilai yang berbeda yaitu pirolisis tanpa katalis (500 ⁰C), dengan katalis 5 wt.% (500 ⁰C), 10 wt.% (400 ⁰C) dan 15 wt.% (550 ⁰C) menghasilkan bio-oil 15,00; 17,92; 16,78; dan 16,54. Penggunaan katalis 5, 10, dan 15 wt.% berat dapat meningkatkan fasa air hasil. Yield char dipengaruhi oleh jumlah katalis hanya pada 300 ⁰C, semakin banyak katalis maka yield char semakin menurun. Pirolisis tanpa katalis menghasilkan produk gas tertinggi. Penggunaan katalis sangat signifikan dalam meningkatkan konversi pirolisis dari 48,69 (tanpa katalis) menjadi 62,46% (katalis 15 wt.%) pada suhu 300 ⁰C. Kondisi optimum untuk menghasilkan minyak nabati terbaik adalah pada 600 °C dengan katalis 10% berat, menghasilkan rasio O/C sebesar 0,14.Kata kunci: C12-4 catalyst, in-situ catalytic pyrolysis, Spirulina platensis residue, yield bio-oil